Integrated analysis of pile groups due to pile eccentricity and pile failure - 1994-, author; Azhar Ahmad, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam) - Universiti Teknologi Malaysia, 2018